Leading names in education: Louis Braille (Journal of Parents and Teachers, 2014)
Louis Braille, inventor of and educational system for blind child, promotioned and improved the quality of education in blind persons. He developed a system based in sixty-three characters constituted by a six points rectangle that makes a concrete figure. This system allows writing, reading and an the access to education with the same opportunities that other child without blind problems.
Keywords: braille; blindness; blind life; leading names on education; education